Classifying strategies for building community health movements: a guide for implementers - Felicia Jia Hui Chan; Alyssa Yenyi Chan; Wen Xi Zhuang; Priyanka Rajendram; Joseph Jie Hui Quek; Weng Mooi Tan; Yoek Ling Yong; Clarice Liying Song; Zoe Jane-Lara Hildon (BMC Public Health)
Abstract Background Enabling community-led health initiatives will contribute to reducing the burdens on the healthcare system. Implementing such initiatives successfully in high and upper-middle income Asian countries is poorly understood and documented. We undertook a Rapid Review, systematically synthesising the evidence to develop implementation guidelines to address this gap. Methods Eligible studies focused on community movements or affiliated constructs in upper-middle and high-income Asian countries, conducted between 2014 and 2021. Studies were sought from either electronic databases – Cochrane and Campbell Collaboration, PubMed, Embase, CINAHL, SCOPUS, APA Psycinfo, Web of Science, Google Scholar – or recommendation from experts. Extraction was undertaken according to mid-level programme goals, termed Intermediate Results. These were conceptualized by a cross-disciplinary team and iteratively reworked as analysis progressed. Framework analysis was undertaken and structured according to the IRs. 28 studies (9 mixed methods, 9 quantitative, 7 qualitative and 3 case studies) were included and synthesised. Results The MovEMENTs checklist and related strategies were elicited through the review. The six Intermediate Results include to: (1) Move the community to be recruited and retained (2) Engage capacity and build capability; (3) Maintain emotional resonance; (4) Embed participatory approaches; (5) Nurture network building and partnerships; (6) Team up to improve commissioning and funding structures. Sixteen strategies and related implementation guidelines underpinning the Intermediate Results are extracted from the evidence-base of included studies. Conclusion The MovEMENTs for Health checklist is developed to serve as a guide for implementers and proposed to be adaptable to various contexts. The checklist should be tested, validated, and updated as a field tool. Trial registration PROSPERO ID: CRD42023471832.